ANALISIS PERBANDINGAN HASIL PEMBUATAN VIRGIN COCONUT OIL (VCO) MENGGUNAKAN PENAMBAHAN RAGI DAN TANPA PENAMBAHAN RAGI - Muhammad Said Karyani (Jurusan Teknik Mesin, 2024)
A comparative analysis of the results of making VCO using the addition of yeast and without using the addition of yeast has been carried out. The method used is a simple experiment, namely measuring the volume of VCO produced and the quality of the product produced (taste, smell, color) with the control variable being the length of fermentation, 1 hour, 3 hours, 5 hours, 7 hours, 9 hours and 11 hours using yeast. fermipan as much as 0.1% and without using yeast. The results show that there is a difference in the growth rate of VCO formation with the addition of yeast and without the addition of yeast. The growth rate of VCO formation using yeast begins to occur during fermentation from the first 1 hour to the next 3 hours, namely the VCO produced starts from 26 mL to 92 mL, after that time interval, in the next 2 hours the growth rate of VCO formation begins to decrease. Meanwhile, the growth of VCO formation without yeast during fermentation since the first 1 hour interval has not occurred significantly, namely only 7 ml of VCO produced. This and the growth of VCO formation only started to increase after 3 hours and then reached 22 ml. Testing the organoleptic properties of the VCO produced, there was no significant difference between the VCO produced with the addition of yeast and without the addition of yeast. Keywords: Virgin Coconut Oil, VCO, Fermentation, Growth Rate, Yeast